NAADP‐regulated two‐pore channels drive phagocytosis through endo‐lysosomal Ca(2+) nanodomains, calcineurin and dynamin - Davis, Lianne C (EMBO J, 2020)
Macrophages clear pathogens by phagocytosis and lysosomes that fuse with phagosomes are traditionally regarded as to a source of membranes and luminal degradative enzymes. Here, we reveal that endo‐lysosomes act as platforms for a new phagocytic signalling pathway in which FcγR activation recruits the second messenger NAADP and thereby promotes the opening of Ca(2+)‐permeable two‐pore channels (TPCs). Remarkably, phagocytosis is driven by these local endo‐lysosomal Ca(2+) nanodomains rather than global cytoplasmic or ER Ca(2+) signals. Motile endolysosomes contact nascent phagosomes to promote phagocytosis, whereas endo‐lysosome immobilization prevents it. We show that TPC‐released Ca(2+) rapidly activates calcineurin, which in turn dephosphorylates and activates the GTPase dynamin‐2. Finally, we find that different endo‐lysosomal Ca(2+) channels play diverse roles, with TPCs providing a universal phagocytic signal for a wide range of particles and TRPML1 being only required for phagocytosis of large targets.